Investigation of Strength and Long-Term Durability Properties of stabilized Coal Mine Overburden Material for Base and Subbase Layer of Pavement - Chandra, Subhash; Sinha, Sanjeev (Engineering, Technology & Applied Science Research, 2024)
The purpose of this study is to examine the possibility of using Coal Mine Overburden (CMOB) material as a secondary aggregate in low volume roadways’ sub-base and/or base layer. Such roads usually experience less traffic, which means that weaker materials like CMOB could be used in various layers of the road after stabilization, either alone or in combination with cement or fly ash. After 7 and 28 days of curing, samples taken from Jharkhand mines were used to assess the strength characteristics of the stabilized samples, namely Unconfined Compressive Strength (UCS) and California Bearing Ratio (CBR). The findings demonstrate that the material, which has CBR of 80% or above and UCS of 3 MPa at 6% for Cement-Treated (CT-CMOB) and Cement-Fly Ash-Treated (CFA-CMOB) samples, may be utilized successfully as a secondary aggregate in low-volume road building. The results were then validated through standard acceptance as per IRC provisions and microstructural analysis. Additionally, correlations were established between the 7 and 28-day UCS properties of CT-CMOB and CFA-CMOB samples. This information can be beneficial for pavement engineers to estimate the strength properties associated with the base and subbase layer of pavement using CMOB as a suitable alternative to conventional aggregates.